2019
DOI: 10.1371/journal.pgen.1008115
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte accumulation regulates the SUMOylation and inclusion dynamics of the prionogenic Cyc8-Tup1 transcription corepressor

Abstract: Environmental stressors can severely perturb cellular homeostasis and compromise viability. To cope with environmental stressors, eukaryotes have developed distinct signaling programs that allow for adaptation during different stress conditions. These programs often require a host of post-translational modifications that alter proteins to elicit appropriate cellular responses. One crucial protein modifier during stress is the small ubiquitin-like modifier SUMO. In many cases, however, the functions of stress d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore, such an ability to control activity of biomolecular motors at the molecular level as demonstrated in this work will greatly contribute to widen the applications of biomolecular motors in nanotechnology. At the same time, this work will motivate further exploration on the role of TMAO and other natural osmolytes in regulating the functions of biomolecular motors and other proteins in living organisms [40,[61][62].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, such an ability to control activity of biomolecular motors at the molecular level as demonstrated in this work will greatly contribute to widen the applications of biomolecular motors in nanotechnology. At the same time, this work will motivate further exploration on the role of TMAO and other natural osmolytes in regulating the functions of biomolecular motors and other proteins in living organisms [40,[61][62].…”
Section: Discussionmentioning
confidence: 95%
“…From a transcriptional perspective, we know from our previous work ( Oeser et al. , 2016 ; Nadel et al. , 2019 ) and other studies ( Zhou et al.…”
Section: Discussionmentioning
confidence: 93%
“…We previously found that sumoylation modulates a transient phase separation in the Tup1-Cyc8 transcriptional co-repressor complex (Oeser et al, 2016), indicating a chromatin-modifying activity for sumoylation during hyperosmotic stress. From a transcriptional perspective, we know from our previous work (Nadel et al, 2019;Oeser et al, 2016) and other studies (Stielow et al, 2008;Zhao, 2018;Zhou et al, 2004) that genes involved either directly in transcription or its modulation have been reported to be sumoylated. How stress-induced sumoylation affects protein activity, localization, or stability remains an open question in the field, and it may be dictated by the magnitude and duration of the stress.…”
Section: Discussionmentioning
confidence: 98%
“…This finding suggests that transcriptional regulation is another mechanism by which SUMO may control lipid metabolism in S. cerevisiae. The physiological significance of the regulation of lipid metabolism by SUMO is not entirely clear but the synthetic lethal phenotypes of erg8 or erg11 mutations in the background of deletions in two E3 ligases, siz1/2, suggest a functional link between SUMO and ergosterol synthesis [24,36,37]. The regulation of the synthesis of sterols and other products of the mevalonate pathway by SUMO in S. cerevisiae represents a mode of regulation conserved among other eukaryotes including C. elegans and mammals as will be discussed below.…”
Section: Yeast-the Regulation Of Lipid Metabolism By Sumo In Eukaryotmentioning
confidence: 99%